Can beavers help improve terrestrial invertebrate diversity? - Andersen, Line Holm; Nummi, Petri; Bahrndorff, Simon (Frontiers in Ecology and Evolution, 2024)
On a global scale, species biodiversity is declining rapidly, including that of terrestrial invertebrates. Environmental heterogeneity is viewed as a key factor promoting biodiversity, and previous studies have shown how beavers can have a profound effect on both habitat heterogeneity and abundance and diversity of a plethora of water-related and terrestrial organisms. However, less is known about the effects of beavers and successional stages on the terrestrial invertebrate community. Here, we review existing knowledge and outline research trajectories to improve our understanding of how beavers affect the terrestrial invertebrate community with special focus on the importance of each successional stage that beavers provide on terrestrial invertebrates. Although beavers can have a large impact on the terrestrial invertebrate community, more studies are needed that take into consideration successional stages and with standardised sampling designs. A better understanding of how beaver activity affects the terrestrial invertebrate community can help in conservation of endangered species and restoration of biodiversity in terrestrial habitats.